PENGARUH EDUKASI MENGGUNAKAN MEDIA FLIPCHART TERHADAP PENGETAHUAN KADER POSYANDU MENGENAI PENCEGAHAN STUNTING (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Stunting not only causes physical growth retardation, but also harms cognitive development. West Java Province (2021) ranks third with 31.09% or 2.7 million children under five being stunted. Tasikmalaya is the district/city with the highest stunting prevalence of 34.37%. Therefore, there is a need for intervention by providing education about stunting prevention through flipchart media. Purpose: Knowing the effect of flipchart media on knowledge of posyandu cadres about stunting prevention in Banyurasa Village, Tasikmalaya Regency. Methods: The research used a quasi experimental design of one group pretest-posttest without control. The sample in this study was the total population of posyandu cadres in Banyurasa Village, Tasikmalaya Regency, which amounted to 31 people. Data analysis used a Paired T-test to prove the research hypothesis. Results: The average score of respondents’ knowledge before given a flipchart is 55,19. The average score of respondents’ knowledge after being given a flipchart is 83,87. The percentage if increased knowledge is 51,96%. The p value on both before and after respondents are given a flipchart is (p=0,000). Conclusion: There was a significant increase in knowledge after been given a education in the flipchart on the stunting prevention of posyandu cadres in Banyurasa Village, Tasikmalaya Regency.